HR Development Strategy and Educator Professionalism - Holilur Rahman; Ilham Abdul Jalil; Firman Ashari; Shophan Readi S (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education plays a strategic role in shaping the character and quality of a nation's human resources, especially in the midst of the era of globalization and rapid technological development. The role of educators is not only limited to the delivery of knowledge, but also involves a deep responsibility in shaping students into individuals who are able to adapt, innovate, and make positive contributions as members of society. The research method that will be utilized is a literature review using a descriptive approach, which involves extracting data and information from various sources contained in the library. Based on the research, results in the form of human resource management, human resource coaching, and the level of professionalism of educators are key elements to achieve organizational goals and educational achievement.